2021
DOI: 10.1111/nph.17384
|View full text |Cite
|
Sign up to set email alerts
|

Shade‐induced reduction of stem nonstructural carbohydrates increases xylem vulnerability to embolism and impedes hydraulic recovery in Populus nigra

Abstract:  Non-structural carbohydrates (NSCs) have been suggested to affect xylem transport under fluctuating water availability, but conclusive evidence is still lacking. We tested the effect of shade-induced NSC depletion on xylem vulnerability to embolism and hydraulic recovery on Populus nigra saplings.  Vulnerability was assessed in light-exposed (L) and shaded (S) plants with the hydraulic method, and in-vivo with the optical method and X-ray MicroCT. Plants were stressed to 80% loss of hydraulic conductance (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 79 publications
1
34
1
2
Order By: Relevance
“…Cochard et al (1999), Lemoine et al (2002), and Herbette et al (2010) also found similar results by air injection or the cavitron, measuring losses in hydraulic conductivity in 2–3 cm long stems in Fagus sylvatica acclimated to sun and shade, although vessel length was not determined. More recently, Populus nigra plants grown under shade conditions had stem P 50 values, measured both hydraulically and optically, which were up to 0.3 MPa less negative than those of stems grown under sun conditions (Tomasella et al, 2021). In this recent work, no anatomical differences in the xylem could explain this shift in P 50 , instead, differences in nonstructural carbohydrates were implicated in this variation (Tomasella et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cochard et al (1999), Lemoine et al (2002), and Herbette et al (2010) also found similar results by air injection or the cavitron, measuring losses in hydraulic conductivity in 2–3 cm long stems in Fagus sylvatica acclimated to sun and shade, although vessel length was not determined. More recently, Populus nigra plants grown under shade conditions had stem P 50 values, measured both hydraulically and optically, which were up to 0.3 MPa less negative than those of stems grown under sun conditions (Tomasella et al, 2021). In this recent work, no anatomical differences in the xylem could explain this shift in P 50 , instead, differences in nonstructural carbohydrates were implicated in this variation (Tomasella et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Populus nigra plants grown under shade conditions had stem P 50 values, measured both hydraulically and optically, which were up to 0.3 MPa less negative than those of stems grown under sun conditions (Tomasella et al, 2021). In this recent work, no anatomical differences in the xylem could explain this shift in P 50 , instead, differences in nonstructural carbohydrates were implicated in this variation (Tomasella et al, 2021). Most of these species used to assess variation in embolism resistance in response to light environment are characterized by relatively vulnerable xylem to embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble NSCs derived from photosynthesis or by starch hydrolysis are also necessary for osmoregulation processes and/or ROS scavenging [46][47][48]90]. Sugars lead to generation of local positive pressures to drive water inflow into embolized conduits when water potential rises upon re-irrigation, leading to hydraulic recovery, i.e., [61,[91][92][93]. In accordance, L. nobilis plants under drought showed a significant increase in soluble NSC content, and a parallel decrease in starch concentration in both C and S samples, compared to well-watered plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above, stem-level photosynthesis might play a primary role not only in the production of NSCs contributing to the whole plant carbon gain but also in the modulation and regulation of xylem hydraulic function. Indeed, some recent studies have reported experimental evidence for a role of stem photosynthesis in reducing xylem vulnerability to embolism and improving the capacity for xylem embolism reversal [59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%